Education for democracy: Articles from the intellectual Anisio Teixeira in the Folha de Sao Paulo newspaper in 1968 - Fernando Gouvêa (Arizona State University, 2016)
The research object in this article is the intellectual thought of Anísio Teixeira in 1968 that opposed the recrudescency of the arbitration government installed in Brazil in 1964. In order to accomplish this research, articles written by the intellectual and published by the newspaper Folha de S. Paulo by June and December 1968 were examined. This topic has not yet been deepened by the historiography of education in Brazil, and thus, this work is affiliated with studies on educational policy and trajectories of intellectuals. The methodology rests on documental and historical research, particularly with regards to cultural history, which values printing as a cultural practice and printed papers as cultural products and representations and political history, which understands the intellectual as a political actor. Regarding the historiographical operation of sources, the following analyses are presented: the contents of the articles; the overlapping of both the increasing violence of the government and the issues covered by the writer; the ideals present in the texts that have permeated Teixeira's work in the course of his intellectual trajectory and also his new concerns; and finally, the contribution of this set of articles for the historiography of Brazilian education, and specifically, points that are still salient for current Brazilian society.